Ecological tax reform initiatives in Africa. (1st January 2015) - Kerckhoven, Sven Van; Bécault, Emilie; Marx, Axel
Ecological Tax Reform (ETR) is featuring high on the policy agenda. The key idea is to shift the tax burden from 'goods', such as productive labour, to 'bads' such as energy use and environmental pollution. Since the 1980s, most OECD countries have installed several environmental taxes and several reports provide an assessment of these instruments. Attention for ETR in developing countries is of a more recent nature and very little information on their ETRs is available. This review paper contributes to the effort by screening nine African countries: Algeria, Benin, Mali, Mozambique, Tanzania, Niger, Senegal, Uganda and South Africa. Data on environmental taxes was collected through various sources. The aim of this paper is to review the current state of the art with regards to environmental taxation in these selected countries. We show that there are currently several interesting initiatives in several countries.